Measurement of b hadron production fractions in 7 TeV pp collisions - Aaji, R; Abellan Beteta, C; Abellan Beteta, C; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Alkhazov, G; et al. (2012)
Measurements of b hadron production ratios in proton-proton collisions at a center-of-mass energy of 7 TeV with an integrated luminosity of 3pb -1 are presented. We study the ratios of strange B meson to light B meson production f s/(f u+f d) and Λb0 baryon to light B meson production f Λb/(f u+f d) as a function of the charmed hadron-muon pair transverse momentum p T and the b hadron pseudorapidity η, for p T between 0 and 14 GeV and η between 2 and 5. We find that f s/(f u+f d) is consistent with being independent of p T and η, and we determine f s/(f u+f d)=0.134±0.004-0.010+0.011, where the first error is statistical and the second systematic. The corresponding ratio f Λb/(f u+f d) is found to be dependent upon the transverse momentum of the charmed hadron-muon pair, f Λb/(f u+f d)=(0.404±0. 017(stat)±0.027(syst)±0.105(Br))×[1-(0.031±0. 004(stat)±0.003(syst))×p T(GeV)], where Br reflects an absolute scale uncertainty due to the poorly known branching fraction B(Λc+→pK -π +). We extract the ratio of strange B meson to light neutral B meson production f s/f d by averaging the result reported here with two previous measurements derived from the relative abundances of B̄s0→Ds+π - to B ̄0→D +K - and B ̄0→ D +π -. We obtain f s/f d=0.267-0. 020+0.021. © 2012 CERN.